ANALISIS PENGARAUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH YANG DIMODERASI OLEH DPK DAN PDB PERIODE 2019 – 2022 (Studi pada Bank Umum Syariah yang Terdaftar di Indonesia) - Prastowo, Guntur Widi (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to determine the effect of mudharabah and musyarakah financing on the profitability of Sharia Commercial Banks which is moderated by Third Party Funds (DPK) and Gross Domestic Product (GDP). This research uses quantitative research with secondary data in the form of panel data on Sharia Commercial Banks (BUS) for the 2019-2022 period. Data processing uses SPSS version 22. The data population in this study is BUS in Indonesia registered with the OJK for the 2019-2022 period. The sampling method used was purposive sampling, namely using several criteria so that there were 7 (seven) Sharia Commercial Banks that became the research sample. The results of this research indicate that mudharabah financing effect on Profitability (ROA), musyarakah financing has an effect on Profitability (ROA), DPK is unable to moderate the effect of mudharabah financing on Profitability (ROA), DPK is unable to moderate the effect of musyarakah financing on Profitability (ROA), GDP is unable to moderate the effect of mudharabah on Profitability (ROA), and GDP are unable to moderate the influence of musyarakah financing on profitability (ROA) in Sharia commercial banks in Indonesia. Keywords: Mudharabah, Musharaka, Profitability (ROA), Third Party Funds (DPK), Gross Domestic Product (GDP)